Safety and efficacy of hydroxy analogue of methionine and its calcium salt (ADRY+®) for all animal species. (20th March 2018) - ; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; de Lourdes Bastos, Maria; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: The European Commission asked EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) to deliver a scientific opinion on the safety and efficacy of ADRY+ ® . ADRY+ ® consists of hydroxy analogue of methionine (HMTBa) and its calcium salt (HMTBa‐Ca), both precursors of l ‐methionine. HMTBa and HMTBa‐Ca are currently authorised for use as a nutritional additives, under the functional group 'amino acids, their salts and analogues'. ADRY+ ® is produced by chemical synthesis and it is intended to be used in feed for all animal species and categories. The FEEDAP Panel concluded that ADRY+ ® is safe for the target animals. The use of the additive in animal nutrition is not expected to result in an accumulation of HMTBa or its metabolites in edible tissues and animal products. Therefore, its use does not raise safety concerns for the consumer. ADRY+ ® is irritant to eyes and not irritant to the skin. The FEEDAP Panel cannot conclude on the skin sensitisation potential of this additive. The exposure of the users to the additive by inhalation is expected to be low. The use of this product as a feed additive does not represent a risk to the environment. ADRY+ ® is an effective source of methionine for protein synthesis in non‐ruminant animals and fish, although HMTBa may show a lower bioefficacy than dl ‐methionine. In ruminants, HMTBa is more slowly degraded in the rumen than dl ‐methionine.